IMPACT OF KNOWLEDGE SHARING BEHAVIOR ON PERFORMANCE OF AUDITING FIRMS IN PAKISTAN: MODERATING ROLE OF ORGANIZATIONAL CULTURE - Munir, Sabra; Imam , Awais; Rasid, Siti Zaleha Abdul; Jamil, Farrukh; Aamir, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to assess how the perceived performance of audit firms is affected by knowledge sharing behaviour (KSB). Additionally, the role of effective organizational culture as a moderator in determination of the intensity of the relationship between KSB and perceived performance is also assessed. For this purpose, data was collected from audit personnel of the big 4 audit firms as well as other “A” ranked accountancy firms in Pakistan via purposive sampling. The survey method which was used was the cross sectional method. Multiple regression and PROCESS macros(Hayes, 2013) were used and analysis of 207 valid responses was done through the use of SPSS software The results obtained were quite revealing in the sense that they showed significant relationship between knowledge sharing behavior and the three dimensions related to it i.e. organizational communication, personal communication as well as communities of practice with organization’s perceived performance. However, no significant relationship was found to exist between written communication and knowledge sharing behavior. At the same time, effective organization culture had a moderating role on the relationship between written communication and organizational communication with organizational perceived performance. This study focused on one type of culture within the auditing firms but it should be taken into account that this is the initial step towards the investigation of the link which KSB and its distinct dimensions have with predicting the performance of eastern audit firm context while considering the role of culture at the same time. Fostering knowledge sharing by the management and the auditors for the improvement of audit practice and the development of a conducive culture for facilitating knowledge sharing.